EFEK DEFOLIASI TERHADAP LAJU PERIMBANGAN TANAMAN UBI JALAR - Edyson Indawan; Reza Prakoso Dwi Julianto; Poppy Indri Hastuti (Agro Bali : Agricultural Journal, 2020)
Defoliation of the leaves of sweet potato plants needs to be done to reduce the rate of vegetative growth, because the rate of vegetative growth that is not balanced with generative growth. The section of the sweet potato plant consists mainly of stems and leaves. The purpose of this study is to obtain sweet potato cultivars with criteria of tubers and stover yields through agronomic experiments with different defoliation and cultivars. Factorial Randomized Design by placing Cultivars as the first factor, (C) included: C₁ (Beta-2), C₂ (Kuningan Merah), C₃ (BIS OP-61-OP-22). The second factor of Defoliated (D), namely : D₁ (Defoliation 16 wap), D₂ (Defoliation 12 wap), D₃ (Defoliation 8 wap), with 3 replications. The results showed that: A high RGR value is followed by a large price URLˊ, meaning that the balance of new plant material is related to the ability of plants to carry out photosynthesis. Cultivar value Beta-2 RGR (8-4) = 71 mg.gˉ¹ dayˉ¹, Kuningan Merah URLˊ(8-12) = 65 mg.cmˉ². BIS OP-61-OP-22 cultivars produce large criteria (51.22 tubers/plot) and medium criteria (44.33 tubers/plot). Beta-2 cultivars produce small criteria (45.56 tubers/plot). Ratio F/R from BIS OP-61-OP-22 cultivars (high dual-purpose), cultivars Beta-2 and Kuningan Merah (high root production)